Yield prediction of boneless cuts, bone and fat trimmings from water buffaloes in Venezuela - Valladares, Oscar Atencio; Leidenz, Nelson Huerta; González, Argenis Rodas; Timaure, Nancy Jerez (Pesquisa Agropecuaria Brasileira, 2007)
The objectives of this study were to determine the association between carcass traits and the percentage yield in boneless cuts (PDC), bone, and fat trimmings of water buffalves; and to develop predicted equations for these variables. Forty-eight crossbred Murrah-Mediterránea buffaloes (24 steers and 24 bulls) were used slaughtered at 17, 19 and 24 months. Carcass and retail-yield-cut traits were evaluated. The following analyses were made: descriptive test, correlation, residual and multiple lineal regression. In castrated animals, subcutaneous fat and circumference round explained the majority of the variation in PDC. The dorsal fat thickness and the renal fat were the variables mostly associated with bone yield. In bulls, the subcutaneous fat and the carcass length explained most of the variation of PDC. The fat trimmings showed the highest correlation coefficient with the subcutaneous fat, and the bone yield was most correlated with the conformation. The equations obtained explained more than 50% of the variation in PCD, however equations for bone yield and fat trimmings showed a higher R2.